Manufacturer Layout Guide on Agricultural Management of Chicken Manure and Charcoal Husk on Growth and the Absorption of Silica in Onions Red (Allium Ascalonicum L.) - Manalu, Chichi Josephine; Habeahan, Chandra (ITScience (Information Technology and Science), 2023)
One effort to reduce the use of inorganic fertilizer is by using organic fertilizer using manure or rice husk charcoal. The research used chicken manure with 3 levels: A0 = 0 kg/plot (0 ton/ha), A1 = 3.75 kg/plot (10 tons/ha), A2 = 7.5 kg/plot (20 tons/ha), A3 = 11.25 kg/plot (30 tons/ha). The second factor, husk charcoal with 3 levels: S0 = 0 kg/plot (0 ton/ha), S1 = 1.9 kg/plot (5 tons/ha), S2 = 3.8 kg/plot (10 tons/ha), S3 = 5.7 kg/plot (15 tons/ha). The results showed that treatment with a dose of chicken manure at 7.5 kg/plot significantly increased leaf length, tuber wet weight per plant, tuber wet weight per plot, tuber dry weight per plant, tuber dry weight per plot, root volume, soil pH. , soil CEC, soil C-organic content, but had no significant effect on the number of bulbs and Si uptake of shallot plants. The activated charcoal dose treatment had no significant effect on leaf length, number of tubers, wet weight of tubers per plant, wet weight of tubers per plot, dry weight of tubers per plant, dry weight of tubers per plot and root volume. The interaction between the dose of chicken manure and husk charcoal had no significant effect on all parameters observed, and had no significant effect on the availability of silica in paddy fields.